Bandwidth management in universities in Zimbabwe: towards a responsible user base through effective policy implementation - Chitanana, Lockias (University of the West Indies, 2019)
This research was undertaken to investigate the issue of how to make more bandwidth available, in particular the research sought to find out about what universities in Zimbabwe are doing to manage their bandwidth. It was, therefore, appropriate to survey a sample of five universities and to catalogue their experiences Results show that successful provision of managed network bandwidth within a university is likely to involve the application of many tools encompassing a number of different techniques. These products are often expensive and are rarely available for loan. Fortunately, a cost-effective solution exists for all universities that can be deployed regardless of the campus' existing wiring or installed devices. The results provided in this paper should help universities to develop and refine usage and access polices as well as plans for network resource allocation.